2017
DOI: 10.1016/j.apmr.2017.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Deliberately Light Interpersonal Contact Affects the Control of Head Stability During Walking in Children and Adolescents With Cerebral Palsy

Abstract: Deliberately light IPT at the apex of the head alters control of head sway in children and adolescents with CP. The effect of IPT varies as a function of contact location and acts differently in TD individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Three nonrandomized studies [21][22][23] were found. After assessment of methodological quality by the ROBINS-I Júnior et al scale, showing strengths in the bias categories after the start of interventions (last four categories), such as deviations from intended interventions, missing data, measurement of outcomes, and selective reporting of results.…”
Section: Study Design and Methodological Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…Three nonrandomized studies [21][22][23] were found. After assessment of methodological quality by the ROBINS-I Júnior et al scale, showing strengths in the bias categories after the start of interventions (last four categories), such as deviations from intended interventions, missing data, measurement of outcomes, and selective reporting of results.…”
Section: Study Design and Methodological Qualitymentioning
confidence: 99%
“…After assessment of methodological quality by the ROBINS-I Júnior et al scale, showing strengths in the bias categories after the start of interventions (last four categories), such as deviations from intended interventions, missing data, measurement of outcomes, and selective reporting of results. However, the three studies failed to adequately address baseline confounding before the interventions began, presenting biases such as the use of a convenience sample with different group sizes 21 , a lack of similarity regarding baseline prognostic factors and type of intervention 22 , and time-varying confounding due to the switch between interventions compared between individuals 23 .…”
Section: Study Design and Methodological Qualitymentioning
confidence: 99%
See 3 more Smart Citations